Recent Publications upon Economics (Quarterly Journal of Economics, 1887)
Journal Article Recent Publications upon Economics Get access The Quarterly Journal of Economics, Volume 2, Issue 1, October 1887, Pages 104–110, https://doi.org/10.1093/qje/2.1.104 Published: 01 October 1887